Ancistrocerus shibuyai (Yasumatsu, 1938), stat. restit. (Hymenoptera: Vespidae: Eumeninae), an overlooked trans-Palaearctic species - Fateryga, Alexander V.; Proshchalykin, Maxim Yu. (Zootaxa, 2024)
Ancistrocerus shibuyai (Yasumatsu, 1938), stat. restit. was hitherto considered a subspecies of A. trifasciatus (Müller, 1776) distributed in Russia (Eastern Siberia, Far East), Mongolia, China (North-East), Korean Peninsula, and Japan, while A. trifasciatus trifasciatus was known to have a nearly trans-Palaearctic distribution. Due to minor but distinct morphological differences between A. shibuyai and A. trifasciatus, the former one is hereby recognized as a separate species. Based on the extensive material examined, A. shibuyai is shown to be widely distributed in the boreal zone of the Palaearctic region; particularly, the species is recorded for the first time from Austria, Ukraine, European part of Russia, Urals, Western Siberia, and Kazakhstan. Ancistrocerus trifasciatus var. moeschleri Blüthgen, 1938, syn. nov. and A. balticus Budrys & Orlovskytė, 2023, syn. nov. are synonymized with A. shibuyai. Distribution and biology of both A. shibuyai and A. trifasciatus are briefly discussed. A lectotype is designated for Odynerus trifasciatus orientalis Kostylev, 1938.